التوجيهات القرآنية في إصلاح التصورات الخاطئة: المرأة المسلمة في ماليزيا نموذجا - Fatin Nurshazana Aznan (al-Jami'ah al-Islamiyah al-'Alamiyah, 2017)
This study aims to explore the wrong perceptions of Malaysian Muslim women. These perceptions were reflected negatively in their behavior. The study will attempt to highlight the Qur'anic approach that could be utilized to correct these perceptions. The researcher tried in this study to uncover the meaning of 'wrong perceptions' their nature, and highlighting the most common ones in several aspects, such as in aqidah (beliefs), ibadah (worship), nikah (marriage), and marital relationship. The researcher has also highlighted the effect of these wrong perceptions on Malaysia Muslim women's behavior. Following a logical sequence, the study highlighted the Qur'anic approach in treating and correcting wrong perceptions in various areas, especially those related to what have been mentioned above. In this study the researcher adopted the deductive method in order to collect the data and handle statistics related to the subject of the study. With regard to correcting wrong perceptions, the deductive research method was also useful. For that purpose, the researcher reviewed relevant Qur'anic verses, traditions of the Prophet, as well as stories of pious Muslim women. The research involved the use of an analytical and critical approach as it attempted to analyze and apply the views and interpretations of early and contemporary Qur'an commentators related to this subject on the Malaysian Muslim society of today. The study concluded that wrong perceptions among Malaysian Muslim women are real phenomena. It also concluded that these perceptions have some real impact on Women behavior. One of the main reasons which contributed to the emergence of this phenomenon is the efforts made by some quarters to corrupt Muslim women and mislead them. The holy Qur'an however, provided the avenues of reform, and encouraged women to follow them. Hence, it secures the society from any potential wrong perceptions.